(untitled) (AYUSHDHARA, 2024)
Ayurveda is a holistic science of life and Aushadha (drug) is an integral part of this Trisutriya Ayurveda. Similarly, according to Ayurvedic classics the treatment’s quadruped (Chikitsa Chatushpada) also gives importance to Aushadha and positioned it next to the physician (Bhishaka). Various drug preparations are mentioned in our classics, and Gunja Taila is one of them described by different Acharyas. It is a Sneha Kalpana made of mainly four ingredients (Gunja, Bhrigraja, Tila Taila and Kanji) and is preferably indicated in Shiroroga. Ayurvedic drugs have the distinct nature of a complex blend of several secondary metabolites. An actual understanding of its ingredients is essential for avoiding adulteration. These medications have their own potential to be utilised both internally and externally, but describing their chemical ingredients and other associated elements is a significant step forward. Rapidly rising efforts in the field of studies of Ayurvedic drugs, in future will result in evidence based Ayurvedic medicine as well as new leads to drug development. In this article an effort is made to review proper identification of raw drugs used for Gunja Taila including understanding of its active ingredients and mode of action.